EDUKASI BERBASIS SEJARAH SIKAT GIGI UNTUK MENUMBUHKAN KEBIASAAN MENYIKAT GIGI YANG BENAR PADA ANAK USIA SEKOLAH DASAR DI SD NEGERI 25 KOTA TERNATE - Lucia Arter Lintang Gritantin; Dhini Yustia Widhyah Saputri; Krida Amalia Husna; Zulhajnie W. Limpas (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Oral and dental health is an essential component of developing clean and healthy living behaviors, particularly among elementary school children. However, limited awareness and understanding of proper dental care remain common issues in primary education settings. This Community Service Program aims to enhance elementary school students’ knowledge and awareness of dental health through an educational approach based on the history and development of toothbrushes. The activity was conducted using interactive learning methods supported by visual media such as posters, toothbrush teaching aids, and educational games to encourage active student participation. The results indicate that students showed high enthusiasm and demonstrated improved understanding of the history of toothbrushes, the function of toothbrushing, and the importance of maintaining oral hygiene from an early age. This program demonstrates that a history-based, visually engaging, and interactive learning approach is effective as a dental health education medium for elementary school students and has the potential to be implemented sustainably within school environments.